The association of plasma connective tissue growth factor levels with left ventricular diastolic dysfunction in patients with overt hyperthyroidism - Li, Huan; Ren, Yahui; Wang, Linfang; Li, Yuming (Frontiers in Endocrinology, 2024)
Background: Left ventricular (LV) diastolic dysfunction is an independent predictor of future cardiovascular events. Early detection of patients with LV diastolic dysfunction can improve clinical outcomes through active management. However, the assessment of diastolic function is very complicated, and there are currently lack of effective biomarkers to assess the risk of LV diastolic dysfunction. Connective tissue growth factor (CTGF) plays a significant role in cardiac remodeling and dysfunction.We aimed to investigate the associations between plasma CTGF level and the risk of LV diastolic dysfunction in this study and judge its effectiveness in diagnosing LV diastolic dysfunction.Methods: A total of 169 patients with overt hyperthyroidism were included. LV diastolic function was evaluated and the subjects were divided into normal LV diastolic function group and LV diastolic dysfunction group. Routine clinical medical data, biochemical data, thyroid related parameters and echocardiographic parameters were recorded for analysis.Results: Compared with normal LV diastolic function group, the LV diastolic dysfunction group had higher age and BMI, as well as lower heart rate, lower serum albumin, lower eGFR, higher serum TgAb and BNP level, and the incidences of hypertension were also higher (all P ＜0.05). Circulating plasma CTGF levels in the LV diastolic dysfunction group were significantly higher (normal LV diastolic function